Análise do processo de convergência de renda na América Latina e no Leste Asiático - Geovana Lorena Bertussi (2008)
Differentiating conditional convergence and club convergence hypotheses is still one of the challenges on convergence empirical literature. The first article addresses this issue, and we investigated which of the convergence hypotheses - absolute, conditional or club - that best describes the movement of the income per worker for the countries of Latin America and East Asia between 1960 and 2000 using the methodology proposed by Johnson and Takeyama (2003). The results demonstrate the relevance of the initial characteristics in the definition of countries' long-term income growth rate, that is, the convergence club hypothesis prevailed on the others and was the most appropriate to describe the evolution of income in the period. In the second paper, we evaluate the income convergence hypothesis (on the same sample of countries and period) through the use of quantile regressions to estimate growth equations. This approach allows us to assess how the effect of policy variables on per worker income growth rate can vary over the conditional growth distribution. The results show that the income convergence process is a local phenomenon, and not a global experience along the conditional growth distribution, that is, each quantile exhibits an income growth behavior that is different from the rest.